2006
DOI: 10.1002/mds.20704
|View full text |Cite
|
Sign up to set email alerts
|

Visual rating of white matter hyperintensities in Parkinson's disease

Abstract: Dementia is a common complication of Parkinson's disease (PD), but the cause is incompletely understood. In previous studies, dementia has been associated with an increase in hyperintense lesions in the cerebral white matter. The aim of this study was to explore whether white matter hyperintensities (WMH) on cerebral magnetic resonance imaging (MRI) are associated with dementia in PD. For this study, 35 patients with PD, 16 with dementia (PDD) and 19 without (PDND), and 20 control subjects were recruited. MRI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
99
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(107 citation statements)
references
References 46 publications
4
99
4
Order By: Relevance
“…These findings should be interpreted with caution, as in addition to the small sample size analyzed, there was no difference in the WMHs burden in PD patients with dementia when compared to control subjects, whilst nondemented patients with PD exhibited fewer WMHs than controls [18].…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…These findings should be interpreted with caution, as in addition to the small sample size analyzed, there was no difference in the WMHs burden in PD patients with dementia when compared to control subjects, whilst nondemented patients with PD exhibited fewer WMHs than controls [18].…”
Section: Discussionmentioning
confidence: 75%
“…Moreover, WMHs have been related to a high risk of MCI and a greater decline in global cognitive performance, executive function, and processing speed [15]. In PD, the relationship between WMHs, MCI, and dementia remains unclear [16][17][18][19]23,34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, frontal type cognitive dysfunctions in patients with MSA may be associated with subcortical cognitive dysfunctions secondary to striatal or subcortical white matter pathology [4,15,17]. Furthermore, Beyer et al [2] reported that WMH was more severe in patients with Parkinson's disease (PD) dementia compared with those with non-demented PD. WMH was the only variable that was significantly associated with minimental state examination score, suggesting that WMH in the deep white matter may contribute to dementia in PD.…”
Section: Discussionmentioning
confidence: 99%
“…The literature on the role of vascular risk factors, and especially on commonly found white matter hyperintensities (WMH) in MRI in elderly PD patients, is rather scarce and inconclusive, finding the contribution to be rather modest [6,7,8] or even absent [9,10,11]. Only a few studies suggest that WMH constitute an independent risk factor associated with cognitive impairment in PD [12,13]. PD as well as Alzheimer's disease (AD) belong to age-related disorders.…”
Section: Introductionmentioning
confidence: 99%